Environmentally Benign Atroposelective Synthesis of Fluorinated Oxindole–Coumarin Hybrid Structures - Bouda, Maria; Xhili, Dea; Hana, Grace E.; Sripada, Archita; Bertke, Jeffery A.; Wolf, Christian (Synlett, 2025)
The significance of multifunctional compounds exhibiting prevalent pharmacophores in the health sciences and increasingly tight manufacturing regulations demand synthetic methods that give efficient access to such scaffolds without resorting to hazardous solvents or additives, expensive reagents or catalysts, and at minimum energy consumption, preferably by avoiding time-consuming and wasteful work-up procedures. Herein, a base-promoted method that produces atropisomeric structures with high diastereoselectivities from fluorooxindoles and 4-chloro-3-nitrocoumarins via dechlorinative Csp2–Csp3 bond formation is described. The reaction occurs under environmentally benign conditions with readily available triethylamine in isopropyl alcohol at room temperature within 1 h. The oxindole–coumarin adducts are obtained in high yields and dr’s up to 37:1 without the need for chromatographic purification.
Keywords: Atroposelective synthesis; Green chemistry; Organofluorines; Oxindoles; Coumarins